Analisis Wacana Islam Dalam Koran Jepang Ito Shinbun - Wibisono, Febri; Haq, Millitania Dienul; Walfajri, Rafif Alhudaibi; Febrianti, Ikromah; Zakiyah, Millatuz (Islamic Insights Journal, 2020)
Mass media is a source of information, one of which is information about religion, including Islam. This study aims to examine how issues about Islam are represented in Japan through the mass media Ito Shinbun. This study uses a descriptive research method with a qualitative approach. Data were collected from articles in the digital version of Ito Shinbun newspaper. Based on the research results it was found that Ito Shinbun represented or reported issues related to Islam in a neutral way. In addition, it is also found that Islamic beliefs are written in Ito Shinbun's news which includes the concept of rejection of LGBT, law and sharia, halal food, and Islamic teachings that do not discriminate against humans